2021
DOI: 10.1101/2021.10.10.463811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Waning grasslands: a quantitative temporal evaluation of the grassland habitats across human-dominated upper Gangetic Plains, north India

Abstract: Grassland habitats currently face severe anthropogenic exploitations leading to cascading effects on the survival of grassland-dependent biodiversity globally, particularly in non-protected areas. Significant amount of such biodiversity-rich grasslands in India are found outside protected areas but lack quantitative information on their status. We evaluated the current and historical (30 years) status of the grasslands using a combination of intensive field surveys and GIS tools across one of the most fertile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 76 publications
(101 reference statements)
1
6
0
Order By: Relevance
“…Despite such loss of habitats, the seasonal movement behaviour of swamp deer (Martin and Gopal 2015) helps maintaining genetic mixing among these fragmented grassland patches, which has earlier been reported as their breeding grounds (Paul et al 2021). This is also evident from the patterns of very low pairwise FST values (between Zones 1 to 5).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Despite such loss of habitats, the seasonal movement behaviour of swamp deer (Martin and Gopal 2015) helps maintaining genetic mixing among these fragmented grassland patches, which has earlier been reported as their breeding grounds (Paul et al 2021). This is also evident from the patterns of very low pairwise FST values (between Zones 1 to 5).…”
Section: Discussionmentioning
confidence: 96%
“…These results support earlier reports of swamp deer congregations during summer months (to feed on young vegetation in the floodplains) and migrations at the onset of monsoon (Schaaf 1978;Qureshi et al 2004). Further, the sugarcane fields possibly help in movement between stopover sights in certain time of the year (Paul et al 2021), as reported from other studies from India (Wikramanayake et al 2004;Athreya et al 2007Athreya et al , 2013Talukdar and Sinha 2013;Warrier et al 2020). It is however important to realise that these inferences are based on only two collared individual females, and future efforts to radio-tag more animals (including both male and females) from different parts of this landscape could help us to ascertain the main drivers of such seasonal movement events.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations